Analisis Efektivitas Sistem Informasi Akuntansi pada Yayasan Global Excellence: Studi Kasus - Hilda, Titi Novia; Syuaib, Haji Mustaqim; Ramadhany, Andi Auliya (Jurnal Liga Ilmu Serantau, 2024)
Accounting Information System (AIS) is a key component within organizations that facilitates the collection, processing, and reporting of financial information. The effective performance of AIS is crucial for organizations to provide accurate and relevant information for decision-making. Yayasan Global Excellence, as a non-profit institution, relies on AIS to manage its finances effectively and meet reporting requirements. This research aims to analyze the effectiveness of implementing the accounting information system at Yayasan Global Excellence and identify constraints that hinder the system's performance in providing necessary information. The research method used is descriptive qualitative analysis. Data collection is conducted through observation of organizational structure, related documents, and financial reports generated by the system. Both primary and secondary data are used to gain a comprehensive understanding of the state of AIS at Yayasan Global Excellence. The analysis results indicate that AIS at Yayasan Global Excellence has not yet met the expected standards for an effective AIS. Several critical aspects such as human resources, technological infrastructure, documentation, procedures, and compliance with accounting standards are not fully met. Therefore, it can be concluded that AIS at Yayasan Global Excellence has not been operating effectively so far. Appropriate improvement measures are needed to enhance the quality of AIS to provide accurate, relevant, and reliable financial information for decision-makers at Yayasan Global Excellence.